2014
DOI: 10.1111/jog.12661
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus: Confusion among medical doctors caused by multiple international criteria

Abstract: Although this study is parochial, its implications are global; that is, further education of caregivers would make the discordant approach to GDM (within and between hospitals) more harmonious and improve the obstetric care of pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…We noted clinical inconsistency in GDM diagnostic criteria used in the prevalence studies we reviewed (Table 4). This corresponds to the common use of existing nonuniform GDM diagnostic criteria in different countries (12,134). Given the importance of the prevalence of GDM in meaningful intervention development, its estimation can be affected by the inclusion of studies that use different GDM diagnosing criteria (137,138).…”
Section: Quality Assessment Of the Gdm Research Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted clinical inconsistency in GDM diagnostic criteria used in the prevalence studies we reviewed (Table 4). This corresponds to the common use of existing nonuniform GDM diagnostic criteria in different countries (12,134). Given the importance of the prevalence of GDM in meaningful intervention development, its estimation can be affected by the inclusion of studies that use different GDM diagnosing criteria (137,138).…”
Section: Quality Assessment Of the Gdm Research Reportsmentioning
confidence: 99%
“…For the entire Eastern Mediterranean region, the existing prevalence estimate of GDM is 14.5%, although this includes only cases diagnosed according to the World Health Organization (WHO) 1999 criteria (4). One previous survey showed that physicians and hospitals in this region use different criteria to diagnose GDM (12).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of GDM has increased with the increasing rates of obesity and diabetes seen worldwide [ 5 , 6 ], and new diagnostic criteria will result in GDM being diagnosed in approximately 18% of all pregnancies [ 7 ]. The diagnosis of GDM, however, is hampered by different criteria used internationally and across different institutions within the same country [ 8 10 ]. Furthermore, as pregnancy outcomes are worse for women with overt DM than for those with GDM, the World Health Organization (WHO) divides hyperglycemia in pregnancy as DM either preceding or first discovered during pregnancy, and GDM, i.e., hyperglycemia during pregnancy which resolves after pregnancy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for pregnant women, gestational diabetes is the primary cause of ketoacidosis. So, if a puerpera suffers from gestational diabetes, with or without symptoms of diabetes mellitus, blood sugar must be effectively controlled, so that the safety of mother and child is fully guaranteed (Agarwal et al, 2015;Lai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%